Critical Analysis of Transformative Interventions Mainstreaming Historically Disadvantaged Black South Africans into the Mining Sector - Kgoale, Peshley Thupane; Odeku, Kola O. (Journal of Reviews on Global Economics, 2018)
Mining in South Africa has experienced racial discrimination with regard to beneficiation. It has primarily benefited white elites during the apartheid era causing undesirable inequality and escalation of poverty for the Black South Africans. Currently, South Africa has one of the highest level of inequality in the world which may be attributed to most of the means of production still being in the hands of white minority. Despite mineral resources being the common heritage of the people of South Africa, both black and white, under the custodianship of the State. Mining has always formed the backbone of South Africa’s economy and in the last two decades it has contributed significantly towards employment and economic growth. But, most of the Historically Disadvantaged Black People have not benefited from it. It is against this backdrop of exclusion that this article examines the innovative minerals interventions introduced to adequately unlock economic potentials of mining for the benefit of the black majority. This article is novel and contributes to the body of knowledge using transformative innovative interventions in the mining industry to mainstream previously denied black majority to take active part in the processes of beneficiation. This article accentuates that to some greater extent, implementation of the interventions would alleviate poverty, promote inclusion and create jobs as the black majority would be able to be part and parcel of exploring, processing and converting mineral resources to finished products and benefit broadly.